Chemistry Learning Revolution: Interactive Multimedia E-Learning with a Problem Based Learning Approach - Triyasmina, Triyasmina; Rusdi, Muhammad; Asyhar, Rayandra; Dachia, Hassan Abdullahi; Rukondo, Nyanjiga (Program Magister Teknologi Pendidikan Universitas Jambi, 2022)
This research aims to develop interactive multimedia e-learning based on problem-based learning in chemistry learning. Research is the development of multimedia that can be a solution in the form of e-learning. Web learning is expected to function as a virtual teacher, virtual classrooms, and learning resources that can be accessed easily. The media was tested in terms of the attractiveness, ease of use, efficiency, and effectiveness. Development carried out by Lee and Owen adaptation models consisting of analysis, design, development, and evaluation. Evaluation phase is done by testing the expert to be validated. Validation is done by a designexperts, media specialist, and a chemistry expert. The products have been valid then tested on students and chemistry teachers in a small group.Based on group tests, it was found that the learning media products developed were liked and received positive responses, so they could be declared good for use as chemistry learning media.